Edukasi Urgensi Ilmu Pembukuan dalam Bisnis bagi Calon Wirausahawan Muda di MAN Lumajang - H Hasrian; Moh. Rifaldi; Amanda Fiorella; Yoga Febianto; Angelina Putri Chetwynd; Hayatul Khairul Rahmat (Yayasan REDI Tiga Monas, 2023)
This community service activity aims to provide education about the urgency of bookkeeping in business for prospective young entrepreneurs at MAN Lumajang. This community service activity is carried out using three methods, namely direct observation, implementation of activities, and evaluation of activities. This community service activity was carried out with good results in that students at MAN Lumajang were able to receive and digest an understanding of the science of bookkeeping in business for prospective young entrepreneurs. This is because bookkeeping is important for a business and is part of accounting records in order to build a new business and become a young entrepreneur in the future.